Business plasticity through disorganization - Herath, Dinuka B.; Secchi, Davide; Homberg, Fabian; Herath, Gayanga B. (Bingley, U.K. : Emerald Publishing Limited, 2019)
Disorganization occurs in all areas of modern business; and yet, disorganization has traditionally been viewed as a negative factor in business and organization performance. However, in a dynamic 21st century environment our conventional structured, rigid responses in dealing with such messiness are not working. Business Plasticity Through Disorganization presents a novel approach to both academics and practitioners on how to break the shackles of rigidity and eliminate our fear of disorganization. Through a chronological discussion of the birth of the concept of 'disorganization' and its gradual evolution into 'business plasticity', the book explores ways in which embracing and leveraging messiness can help improve the way we create, innovate and run our businesses.Challenging existing theories and approaches to disorganization, as well as presenting new evidence from both research and practice, Herath promotes new conceptual thinking aimed at promoting flexible 'plasticity' in the modern organization to build greater functional capability globally.
Prelims -- Chapter 1: Sorting the "mess" from the rest -- Section A: Origins -- Chapter 2: The problem with "order" -- Chapter 3: Birth of disorganization -- Section B: Understanding disorganization -- Chapter 4: The logic of disorganization -- Chapter 5: Coping with stochasticity -- Chapter 6: Order in chaos -- Section C: Implementing disorganization -- Chapter 7: Goal-driven disorganization -- Chapter 8: Structural disorganization -- Chapter 9: Functional disorganization -- Section D: Towards business plasticity -- Chapter 10: Business plasticity -- Chapter 11: Toward plasticity: disorganization as a sustainable capability -- Section E: Implications -- Chapter 12: Future of disorganization: a research agenda for scholars -- Chapter 13: Studying the cognitive elements of disorganization -- Chapter 14: Lessons for practice on the relevance of the study of "disorganization" for practitioners -- Chapter 15: At the end of day -- References -- Index.
Includes bibliographical references and index.
Print version record
Keywords: Organizational behavior; Industrial organization; Business & Economics -- Organizational Behavior; Business & management